Performance Evaluation of Cryptographic Algorithms over IoT Platforms and Operating Systems. (23rd August 2017) - Pereira, Geovandro C. C. F.; Alves, Renan C. A.; Silva, Felipe L. da; Azevedo, Roberto M.; Albertini, Bruno C.; Margi, Cíntia B.
Abstract : The deployment of security services over Wireless Sensor Networks (WSN) and IoT devices brings significant processing and energy consumption overheads. These overheads are mainly determined by algorithmic efficiency, quality of implementation, and operating system. Benchmarks of symmetric primitives exist in the literature for WSN platforms but they are mostly focused on single platforms or single operating systems. Moreover, they are not up to date with respect to implementations and/or operating systems versions which had significant progress. Herein, we provide time and energy benchmarks of reference implementations for different platforms and operating systems and analyze their impact. Moreover, we not only give the first benchmark results of symmetric cryptography for the Intel Edison IoT platform but also describe a methodology of how to measure energy consumption on that platform.